Microservice system based on container cloud - Di YANG (Dianxin kexue)
Lack of the procedure of deploying containerized services in microservice systems,the continuous delivery only put executable codes or programs to the production environment.There is no solution for problems of the test version and configuration updates.The microservice system based on container cloud was proposed.Continuous integration for containerized services and the method that supports debugging tests for multi-version of multi-services were designed.Goals of non-stop production and seamless switch between versions were achieved.These services were monitored and managed by an operation and maintenance platform.After production environment verification,the proposed system supports services running without stop and immediate response and satisfies the needs of production.